ANALYSIS OF CUSTOMER SATISFACTION ANGKRINGAN MBAH SINGO NGANJUK EAST JAVA - Ghufrani Rifqi, Imelda; Widodo, Joko; Zulianto, Mukhamad (Program Studi Magister Manajemen Universitas Advent Indonesia, 2024)
Angkringan Mbah Singo Nganjuk located in Nganjuk Regency, Jl. Attorney General Suprapto No. 29, Kauman, Kec. Nganjuk Since February 2015. This research analyzed customer satisfaction with Angkringan Mbah Singo based on service quality, product, and price. Aims to examine the level of customer satisfaction at Angkringan Mbah Singo Nganjuk. The author uses descriptive qualitative research methods with data sources in the form of principal and supporting data sources. The collection technique is conducted by interviewing customers and owners of Angkringan Mbah Singo Nganjuk. The results showed that the customers were satisfied with the service, prices, and products. Customer satisfaction analysis is seen through service, product, and price. Based on the research results, the service employees provide to customers is considered quite good, but they still need to pay attention to service when conditions are busy. The products served have good quality taste and hygiene, and some menus are only available once a few weeks. This makes customers feel disappointed when looking for these products. The price of Angkringan Mbah Singo Nganjuk's products is considered cheap and fits into the general public, from school children to employees.